Editors’ Word - Ejdus, Filip; Džuverović Nemanja; Kovačević, Marko; Vujinović, Nikola (Journal of Regional Security, 2018)
A glance look at the key international news suggests that world politics is not only the struggle about the present or the future, but to a striking extent, it is also a struggle about the past. However, mnemonic battles are not epiphenomena to the geopolitical competition and war, but their constitutive part. It is only through a certain vision of the past, through a particular collective memory that polities make sense of who they are, how they perceive national security and what they want in world politics. This issue of Journal of Regional Security deals with different aspects of the interdependence of identity, memory and security.